2016
DOI: 10.1016/j.jsat.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Cost of Clinical Supervision for Motivational Interviewing: A Randomized Controlled Trial

Abstract: The effectiveness of a competency-based supervision approach called Motivational Interviewing Assessment: Supervisory Tools for Enhancing Proficiency (MIA: STEP) was compared to Supervision-As-Usual (SAU) for increasing clinicians’ motivational interviewing (MI) adherence and competence and client retention and primary substance abstinence in a multisite Hybrid Type 2 effectiveness-implementation randomized controlled trial. Participants were 66 clinicians and 450 clients within one of eleven outpatient substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 82 publications
0
71
0
2
Order By: Relevance
“…Miller, Yahne, Moyers, Martinez, & Pirritano, 2004; Schoenwald, Sheidow, & Chapman, 2009), including CBT (Rakovshik, McManus, Vazquez-Montes, Muse, & Ougrin, 2016; Rakovshik et al, 2013; Sholomskas et al, 2005). The lack of supervision and monitoring of clinician implementation of evidence-based treatments in clinical practice suggests that CBT and other EBPs, in practice, may bear little resemblance to the more closely monitored versions of those treatments as implemented in randomized clinical trials demonstrating their efficacy (Martino et al, 2016). …”
Section: Stage 3 and Beyond: Dissemination And Its Challengesmentioning
confidence: 99%
“…Miller, Yahne, Moyers, Martinez, & Pirritano, 2004; Schoenwald, Sheidow, & Chapman, 2009), including CBT (Rakovshik, McManus, Vazquez-Montes, Muse, & Ougrin, 2016; Rakovshik et al, 2013; Sholomskas et al, 2005). The lack of supervision and monitoring of clinician implementation of evidence-based treatments in clinical practice suggests that CBT and other EBPs, in practice, may bear little resemblance to the more closely monitored versions of those treatments as implemented in randomized clinical trials demonstrating their efficacy (Martino et al, 2016). …”
Section: Stage 3 and Beyond: Dissemination And Its Challengesmentioning
confidence: 99%
“…Referring to audio or video tapes enables the supervisee to receive specific competencebased feedback, which is considered relevant for skills development [23]. Comparing supervision based on verbal reports (i.e., supervision as usual) with those based on video recordings of therapy sessions, Martino et al [24] demonstrated that the latter contributed more to competence development. Even so, regarding clinical supervision, only a limited number of systematic and controlled studies have been published to date [12,25].…”
Section: Active Versus Passive Strategiesmentioning
confidence: 99%
“…Considering prior studies [24,52], we assume moderate competence differences between the groups (Cohens d = 0.60) and high correlations between competence ratings (r = 0.50). Given an α of 0.05 and a 1-β of 0.80 (power), a sample of 68 participants will be necessary in each experiment, resulting in an overall sample size of 136 (G*Power Version 3.1.9.2) [53].…”
Section: Statistical Analysis and Power Calculationmentioning
confidence: 99%
“…The currently accepted method of training typically involves attending a specialist workshop, reading relevant texts and a subsequent period of supervision from someone expert in the treatment [6]. As this method is both labour-intensive and costly [7,8] and vulnerable to the shortage of treatment experts it limits the number of therapists that can be trained and therefore the number of people who might potentially receive effective treatment.…”
Section: Introductionmentioning
confidence: 99%